2018
DOI: 10.1007/s13201-018-0649-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hydrogeochemical status of groundwater in a coastal region of Southeast coast of India

Abstract: A study was conducted in a coastal region of Cuddalore district of Tamil Nadu, India, to identify the hydrogeochemical processes controlling the groundwater chemistry. The major geological units of the study area are sandstone, clay, alluvium, and laterite soils of Tertiary and Quaternary age. A total of 64 groundwater samples were measured for major ions and stable isotopes. Higher electrical conductivity values indicate the poor quality groundwater along the coastal region. Saline water intrusion mainly affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…This finding also matches with Khanom and Salehin (2012). High EC values indicate poor quality drinking water that threatens environmental and public health (Bangladesh Water Act, 2013;Minar et al, 2013;Chidambaram et al, 2018). The present investigation revealed that most drinking water sources contained high concentrations of Fe.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This finding also matches with Khanom and Salehin (2012). High EC values indicate poor quality drinking water that threatens environmental and public health (Bangladesh Water Act, 2013;Minar et al, 2013;Chidambaram et al, 2018). The present investigation revealed that most drinking water sources contained high concentrations of Fe.…”
Section: Discussionsupporting
confidence: 85%
“…The hydrological system in the coastal area is influenced by seawater and hydro-geochemical processes that are leading to deteriorating drinking water quality in groundwater systems (Chidambaram et al, 2018). In the tidal delta plain of south-western Bangladesh, high salinity and Arsenic (As) concentrations in groundwater is a widespread problem (Ayers et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca-Cl is the major water type in the study are, which indicates the dissolution of ions by the monsoonal rainfall recharge [51]. Gibbs plot also indicate the dominance of weathering process by the water-rock interaction through the recharge water [52]. Overall, the higher concentration of ions in groundwater at the discharge region (i.e.…”
Section: Major Ionsmentioning
confidence: 79%
“…Water studies in wetlands tend to be limited to surface water (Kors et al, 2012) and, occasionally, to interstitial water (water present at the root level, Weterbach et al, 2016), without understanding the role of groundwater in wetlands, its chemical composition, or the hydrogeochemical processes influencing these ecosystems (Hunt, Krabbenhoft, & Anderson, 1997;Liu & Mou, 2016). With respect to hydrogeochemical studies in coastal areas, this have been carried out to understand the water quality of aquifers for human use (Chidambaram et al, 2018;Lee & Song, 2007) and, more recently, to identify the causes of salinization (salt intrusion, geological processes, or anthropic contamination, Böhlke & Denver, 1995;Lee & Song, 2007;Bouzurra, Bouhlila, Elango, Slama, & Ouslati, 2017). Some hydrogeochemical studies have been focused to understand dynamics between groundwater and surface water to reduce anthropic effects but without an ecological approximation (Ladouche & Weng, 2005).…”
Section: Introductionmentioning
confidence: 99%